Raising dairy productivity in Tanzania through better husbandry and feed - International Livestock Research Institute (International Livestock Research Institute, 2019)
Mbeya, Tanzania. After regularly providing his cows with adequate shelter and high quality balanced feed, Abel Mwandemange sees milk production in his cows significantly increase. Abel is one of thousands of dairy farmers in Tanzania who received good husbandry and feed training under ILRI-led African Dairy Genetic Gains (ADGG) program in Tanzania. ADGG is working to unlock the potential of Tanzania's dairy sector by identifying and delivering more productive and profitable dairy cows. The ADGG program is a collaboration of Tanzanian and international partners, and is supported by the Bill & Melinda Gates Foundation & the CGIAR Research Program on Livestock. Learn more: http://news.ilri.org/category/ilri/adgg/